The Antiviral Effects of Sodium Phenylbutyrate Against BoHV-1 Infection In Vitro - Chen, Xinye; Zhu, Guoqiang; Zhu, Liqian (Letters in Drug Design & Discovery, 2019)
Introduction: The alteration of histone acetylation is a known mechanism to regulate gene expression, and thereby affecting various cellular processes. Histone deacetylases (HDACs) are known to regulate histone acetylation by removal of the acetyl group from lysines. HDAC inhibitor such as Sodium Phenylbutyrate (PB) and Valproic Acid (VPA) have been reported to affect multiple virus infection while whether they affect BoHV-1 infection is unknown. Objectives: The aim of the study is to investigate whether PB and VPA effects BoHV-1 infection and the virus induced inflammation related signaling including Erk1/2 and p38MAPK signaling. Methods: To assess the antiviral effects of PB and VPA on BoHV-1 infection, MDBK cells were treated with these inhibitors at different concentrations. Then time addition was performed to pinpoint which stages of virus infection was affected by the chemicals. In order to assess whether PB affect viral gene expression, we detected the viral IE genes such as bICP0, bICP4 and bICP22 using real-time PCR assay. The effects of PB had on the activation of inflammation related signaling including Erk1/2 and p38MAPK in response to the virus infection were also detected. Results: Here, for the first time we reveals that PB but not VPA affects BoHV-1 infection at late stages of infection. It affected the expression of IE genes such as bICP0, bICP4 and bICP22. Interestingly, PB enhanced the activation of both Erk1/2 and p38MAPK signaling stimulated by BoHV-1 infection. Conclusion: HDAC inhibitor PB significantly inhibited BoHV-1 infection partially through the interruption of certain viral IE gene expression. Though PB has been reported to have antiinflammatory effects, we found that it enhanced the activation of inflammation pertinent signaling of both Erk1/2 and p38MAPK stimulated by BoHV-1 infection.
Keywords: valproic acid